KEPEMIMPINAN PENYULUH AGAMA ISLAM DALAM PEMBINAAN PENDIDIKAN INFORMAL MASYARAKAT MUSLIM DI KOTA SORONG - Radjaang, Nasruddin (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2022)
This study uses a type of descriptive qualitative research located in North Sorong District. This research approach is the guidance approach and the sociological approach. Primary data sources in this study were Islamic Religious Extension as key informants and additional informants, namely youth and community leaders. Secondary data sources in this study are books, magazines, internet, reports and documentation. Data collection methods used are observation, interviews, and documentation. Analysis of this research data through data reduction, data presentation and drawing conclusions. The results showed that the leadership role played by Islamic religious instructors in informal education for the Muslim community in North Sorong District was carrying out routine recitations, eradicating illiteracy in reading and writing the Koran and acting as an informant, consultant and advocate. The inhibiting factors for Islamic religious instructors in informal education for Muslim communities in North Sorong District are the misuse of social media and technology, the lack of discipline and the seriousness of society. Then, the solution provided by Islamic religious instructors is to optimize recitation activities, provide school financing through foster parents, provide motivation and guidance and familiarize children with carrying out Islamic teachings properly.